(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The study of predicates in linguistics is central to understanding sentence structure and meaning. Predicates are crucial componentsof a sentence as they typically express actions, states, or processes that are attributed to the subject. This article explores the communicative-functional properties of predicates, examining how predicates contribute to the information conveyed in a sentence and their role in the communicative process. By analyzing different linguistic theories and perspectives, we highlight the interaction between syntax, semantics, and pragmatics in determining the communicative function of predicates. Examples from various languages demonstrate the versatility and functional importance of predicates in structuring meaningful and contextuallyappropriate utterances